Knowledge, attitudes, practice and behaviour of nurses caring for HIV/AIDS patients at public hospitals in the Tshwane Metropolitan area - Shabani, Omari (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.